Prevalence and relevance of the positivity of skin prick testing in patients with chronic urticaria - Kanokvalai Kulthanan (2018)
Many patients with chronic urticaria (CU) worry that foods or other allergens are responsible for their urticaria. Skin prick testing (SPT) may be one of the investigations used to provide a clear illustration. The purpose of our study was to assess the prevalence of positivity of SPT to food allergens and aeroallergens and their relevance in patients with CU, in order to demonstrate the diagnostic value of SPT in CU. We retrospectively reviewed case record forms of patients with chronic ordinary urticaria who underwent SPT in the Urticaria Clinic, Siriraj Hospital, during the period 2000-2004. The studied allergens included 16 food allergens and 12 aeroallergens. Eighty-eight patients were enrolled. The prevalence of positive SPT among patients with CU was 47.7%. Patients who had personal histories of atopy had statistically significant positive SPT results compared with patients who had negative SPT. Of 88 patients, 26 patients (30%) gave positive results to food allergens, 36 patients (41%) gave positive results to aeroallergens and 20 patients (22.7%) gave positive results to both food and aeroallergens. One-third of the subjects (34.6%) who had positive SPT results to food allergens had clinical relevance of food allergy in some systems but only one patient had clinical relevance of food-induced urticaria. Half of the patients who had a history of aeroallergen sensitivity gave a positive SPT response for aeroallergens; however, there was no clinical relevance to their CU. Our study showed that the prevalence of positive SPT to food allergens and aeroallergens in patients with CU was common but had little clinical relevance to CU. © 2008 Japanese Dermatological Association.